Bioimpedance vector analysis of elite, subelite, and low-level male volleyball players - Campa, F.; Toselli, S. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To establish a specific player profile on body-composition parameters and to provide a data set of bioelectric impedances values for male volleyball players. Methods: The study included 201 athletes (age 26.1 [5.4] y, height 191.9 [9.7] cm, weight 86.8 [10.8] kg) registered in the Italian volleyball divisions. The athletes were divided into 3 groups: The elite group comprised 75 players participating in the 1st (Super Lega) division, the subelite group included 65 athletes performing in the 2nd (Serie A2) division, and the low-level group included 61 players participating in the 3rd (Serie B) division. Bioelectric impedance, body weight, and height of the athletes were measured in the second half of the competitive season. In addition, bioelectrical impedance vector analysis was performed. Results: The elite group showed a greater amount of fat-free mass (FFM) and total body water (TBW) and a lower fat mass (FM) than the subelite group (P<.05). In addition, the elite players were taller and heavier and had a higher FFM, FM, TBW, and body cellular mass than the low-level athletes (P<.05). Finally, the mean impedance vectors of the elite group significantly differed from those measured in the normal population and in the other 2 groups (P<.05). Conclusions: This study provides an original data set of body-composition and bioelectric impedance reference values of elite male volleyball players. The results might be useful for interpretation of individual bioimpedance vectors and for defining target regions for volleyball players.